Department of a University and Social Sphere of the Region - O. E. Shapovalova; N. V. Shklyar (Moscow Polytechnic University, 2019)
One of the main structural units of the University is the Department. Its quality largely determines the image of the institution of higher education, its attractiveness for potential students. Special importance is given to the profiling, graduating Department, organizing research work and practical training of students. In this regard, this article summarizes the five-year experience of one of the departments of the regional University in the aspect of optimization and meeting the social demands to education. The leading method of research is a systematic analysis of the main activities of the Department of correctional pedagogy, psychology and speech therapy, staffed by highly qualified specialists. The article presents the most significant achievements of this Department, which justify its impact on the sphere of educational needs of society. Throughout the considered time period, the Department of correctional pedagogy, psychologists and speech therapy conducted training and retraining of psychological and pedagogical personnel soughed after in the Jewish Autonomous region for the system of special and inclusive education for persons with disabilities. At the same time the Department carried out an effective scientific and practical interaction with the pedagogical community of the region. The materials and results of the presented study were experimentally tested, implemented in the educational process and repeatedly discussed at the meetings of the Department, as well as during scientific seminars and conferences. The gained experience can be useful for managers and scholars of the departments.